Community Participation in Child and Juvenile Delinquents Care - Teeraphan, Papontee; Pankaew, Panuwat (Naresuan University Law Journal, 2021)
Juvenile and Family Court and Procedure Act B.E. 2553 (2010), allows a community to participate in the process of rehabilitation plan-making in both pre-trial and post-trail. Public participation under the law, however, still has 3 problems. Firstly, it is the problem that the discretion of the director of juvenile observation and protection center is allowed to use to invite the community representative to join the rehabilitation plan making meeting. Secondly, it is the problem of the form of participation to care for the child and juvenile delinquents. Thirdly, it is the level of that community participation in child and juvenile delinquents’ care. Therefore, Juvenile and Family Court and Procedure Act B.E. 2553 (2010) should be amended to develop and encourage community participation in child and juvenile delinquents care by not giving the discretion to the director of juvenile observation and protection center. It should order the community representative to be a committee and to join the rehabilitation plan making meeting. There also should not be a limitation in the process of plan-making and action taking only, but following-up and assessment should be freely allowed. The law, moreover, should be amended or developed to allow the community to care for the child and juvenile delinquents as they expected and are ready.